Unravelling the complex structure of forest soil food webs: higher omnivory and more trophic levels. Issue 10 (12th June 2014) - Digel, Christoph; Curtsdotter, Alva; Riede, Jens; Klarner, Bernhard; Brose, Ulrich
<x xml:space="preserve">Abstract</x> Food web topologies depict the community structure as distributions of feeding interactions across populations. Although the soil ecosystem provides important functions for aboveground ecosystems, data on complex soil food webs is notoriously scarce, most likely due to the difficulty of sampling and characterizing the system. To fill this gap we assembled the complex food webs of 48 forest soil communities. The food webs comprise 89 to 168 taxa and 729 to 3344 feeding interactions. The feeding links were established by combining several molecular methods (stable isotope, fatty acid and molecular gut content analyses) with feeding trials and literature data. First, we addressed whether soil food webs (n = 48) differ significantly from those of other ecosystem types (aquatic and terrestrial aboveground, n = 77) by comparing 22 food web parameters. We found that our soil food webs are characterized by many omnivorous and cannibalistic species, more trophic chains and intraguild‐predation motifs than other food webs and high average and maximum trophic levels. Despite this, we also found that soil food webs have a similar connectance as other ecosystems, but interestingly a higher link density and clustering coefficient. These differences in network structure to other ecosystem types may be a result of ecosystem specific constraints on hunting and feeding characteristics of the species that emerge as network parameters at the food‐web level. In a second analysis of land‐use effects, we found significant but only small differences of soil food web structure between different beech and coniferous forest types, which may be explained by generally strong selection effects of the soil that are independent of human land use. Overall, our study has unravelled some systematic structures of soil food‐webs, which extends our mechanistic understanding how environmental characteristics of the soil ecosystem determine patterns at the community level.